2005
DOI: 10.2308/accr.2005.80.2.649
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee Quality and Internal Control: An Empirical Analysis

Abstract: I examine the association between audit committee quality and the quality of corporate internal control. While information on the quality of internal control is not generally available, companies changing auditors are required to disclose any internal control problems that were pointed out by their predecessor auditors. The empirical results are based on a comparison of companies disclosing such internal control problems with a control sample of companies changing auditors but not disclosing internal control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
617
2
31

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(676 citation statements)
references
References 35 publications
26
617
2
31
Order By: Relevance
“…The composition and functions of the committee can be used as observable features that influence its effectiveness. Such features include, for example, the independence of the members of the audit committee (Chan and Li, 2008, Krishnan, 2005, Balasubramanian et al, 2010, and the chairperson of the board not being a member/chairperson of the audit committee (South Africa IOD, 2009).…”
Section: Board Of Directorsmentioning
confidence: 99%
“…The composition and functions of the committee can be used as observable features that influence its effectiveness. Such features include, for example, the independence of the members of the audit committee (Chan and Li, 2008, Krishnan, 2005, Balasubramanian et al, 2010, and the chairperson of the board not being a member/chairperson of the audit committee (South Africa IOD, 2009).…”
Section: Board Of Directorsmentioning
confidence: 99%
“…The following studies confirming the results of this study. Krishnan (2005) examines the period prior to the enactment of SOX, when internal control problems are only disclosed in 8-Ks filed by firms when changing auditors. With information collected from 8-K filings, she finds that independent audit committees and audit committees with more financial expertise are significantly less likely to be associated with the incidence of internal control problems (Ziaee, 2014).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Since an entity's internal control is under the purview of its audit (Krishnan, 2005), we investigate the relation between audit quality and internal control weaknesses. In a similar study Imam and Malek (2007) examined the relationship among ownership structure and firms' performance and dividend policy.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Farber (2005) finds that firms subject to an SEC enforcement action have fewer financial experts on their audit committees than a control group of similar firms. Similarly, Krishnan (2005) documents that the financial expertise of audit committee members is negatively related to the incidence of internal control problems. Zhang et al (2007) also provide evidence that firms are more likely to be identified with an internal control weakness under SOX if their audit committees have less financial expertise.…”
Section: Chapter II Literature Review and Hypothesis Developmentmentioning
confidence: 99%